Dynamic evolution control for the DC/DC boost converter design and implementation - Samosir, Ahmad Saudi; Sulistiyanti, Sri Ratna; Gusmedi, Herri; Mardiyah, Luthfiyyatun (Institute of Advanced Engineering and Science, 2024)
This paper introduces the design and hardware implementation of the dynamic evolution control for a DC/DC boost converter. The development of the controller aims to effectively regulate the output voltage of the DC/DC boost converter with a high degree of precision. A comprehensive examination of the duty cycle formula for the boost converter is conducted using a non-linear analysis approach. This study introduces a methodology for the synthesis of a converter controller utilizing the principles of dynamic evolution control theory. The converter's output consistently aligns with the target voltage by following the dynamic evolution path determined by the designed controller. The performance evaluation of the proposed boost converter controller utilizing dynamic evolution control is being validated through the utilization of MATLAB/Simulink simulation software. The effectiveness of the proposed controller is further validated through the presentation of hardware results. The performance of the controller was evaluated by varying the values of parameters k and m.